Effects of Integrase Inhibitor–Based ART on the NLRP3 Inflammasome Among ART-Naïve People With HIV. (29th September 2020) - Toribio, Mabel; Burdo, Tricia H; Fulda, Evelynne S; Cetlin, Madeline; Chu, Sarah M; Feldpausch, Meghan N; Robbins, Gregory K; Neilan, Tomas G; Melbourne, Kathleen; Grinspoon, Steven K; Zanni, Markella V
Abstract: The NOD-like receptor protein family pyrin domain containing 3 (NLRP3) inflammasome, activated in the setting of HIV, contributes to pro-atherogenic inflammation. Among antriretroviral therapy–naïve people with HIV (vs controls), levels of caspase-1—a key component of the NLRP3 inflammasome—were significantly increased. Six months of elvitegravir/cobicistat/emtricitabine/tenofovir disoproxil fumarate significantly decreased caspase-1 levels in association with CD4+/CD8+ ratio recovery. Trial registration . ClinicalTrials.gov NCT 01766726.